Specific features of state support for compatriots abroad: legal analysis (Journal of actual problems of jurisprudence, 2021)
The relevance of the topic under study is due to the fact that compatriots abroad and the related problems of migration and immigration are distinguished by the transition from a socio-economic, cultural phenomenon to a political one. In this regard, it is expected that geopolitical changes will lead to new waves of migration and the need for legal regulation of issues related to state support for compatriots abroad. This issue is undoubtedly relevant for Kazakhstan as well. Thus, the policy of state support for Kazakhs abroad has recently been significantly updated in connection with the narrowing of the scope of the Kazakh language and the threat of gradual loss and assimilation of the original national identity of Kazakhs in their countries of residence.The main purpose of the research is to study problematic issues of legal regulation of state support for compatriots abroad, as well as preparation of relevant proposals based on the study of international experience, since at present in Kazakhstan support of foreign compatriots is not regulated from a legal point of view, which does not correspond to international practice.The scientific and practical significance of the study lies in the fact that the issues of state support for compatriots abroad, primarily the Kazakh diaspora, are considered, that is, on the one hand, the current state of state policy and national legislation, on the other, modern international experience. The article, to a greater extent, focuses on the legal regulation of this issue. In addition, the study of issues of support for compatriots abroad is closely related to such components as the diaspora, the migration process, and in this regard, they were also considered.The methodological basis of the research is: general scientific methods (logical, structural and systems analysis, synthesis, comparison, abstraction, induction and deduction, modeling), as well as special methods and techniques for studying phenomena and processes (concrete historical, dialectical, formal-logical, structural-functional, method of comparative jurisprudence).As a result of the study, taking into account the world experience, for the first time in Kazakhstan the necessity of adopting a special law regulating the issues of state support of compatriots abroad was substantiated.Keywords: state support, compatriots abroad, diaspora, migration, international experience, legislation